Post‐synthetic Chemical Fixation of Fe2+ in MOF to Prepare Fe2N‐Embedded N‐Doped Graphene Nanoribbons for Superior Oxygen Reduction Reaction. Issue 7 (3rd March 2023) - Xu, Wenli; Yang, Limeng; Li, Liangjun; Shao, Junwei; Liu, Tao; Xing, Tao; Wang, Muzhou; Li, Zhi; Wu, Mingbo
Abstract: The construction of efficient non‐precious metal electrocatalysts for oxygen reduction reaction (ORR) with controlled structures and active sites is of fundamental importance for the wide utilization of hydrogen fuel cells. Herein, we report a controllable chemical fixation strategy that enables the simultaneous optimization in both of local and external structure of the Fe−N−C catalyst. The post‐synthetic single‐atomic chemical fixation of Fe 2+ ions in coordinated‐free bi‐pyridine sites combined with the carbonation afford a Fe2 N‐embedded N‐doped graphene nanoribbon (Fe2 N/NGNR) with dispersing Fe2 N nanoparticles embedded in NGNR. When used as ORR electrocatalyst, Fe2 N/NGNR exhibits a half‐wave potential of 0.87 V and 0.79 V vs. RHE in alkaline and acid medium, respectively, comparable to commercial Pt/C (20 wt%) catalysts. The prominent ORR activity of Fe2 N/NGNR is verified an H2 ‐O2 fuel cell which displayed a peak power density of 307.7 mW/cm 2 when using the Fe2 N/NGNR as the catalyst in the cathode electrode. Abstract : A controllable chemical fixation strategy that enables the simultaneous optimization in both of local and external structure of the Fe−N−C catalyst was reported.